THE THE EFFECT OF PLYOMETRIC TRAINING ON VERTICAL JUMP SKILLS OF VOLLEYBALL EXTRACURRICULAR PARTICIPANTS AT SMAN 4 PANDEGLANG: An Experimental Study on High School Volleyball Athletes - Rusmiyadi; Sukron Ma'mun; Moh Alfharizi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine the effect of plyometric training on vertical jump ability in volleyball extracurricular participants of SMAN 4 Pandeglang. The plyometric training method is suspected to have an influence on improving vertical jump skills in volleyball extracurricular participants of SMAN 4 Pandeglang. This study is a pure experimental research, with the designs used in this study being True pretest experiments and Post-test Design. The sample in this study is students participating in the men's volleyball extracurricular, with a total of 20 people. Data collection was carried out using tests, with Vertical Jump instruments. This data analysis technique uses t-test analysis through normality and homogeneity prerequisite tests. The results of hypothesis testing using the t- test obtained a calculated T of 13.652 and a table T value of 1.734, and Sig=0.000. Then the calculated T value is greater than the T table (13.652>1.734) or Sig is smaller than 0.05 (Sig<0.05). So there is a significant difference between the data before and after the treatment. The increase was evident because there was an average increase of 4.25 from 56.70 to 60.95. If expressed as a percentage, the increase is 7.49%. Thus, it can be concluded that there is a significant influence in plyometric training on vertical jump skills in volleyball extracurricular participants of SMAN 4 Pandeglang.